KARAKTER TOKOH DALAM NOVEL SUNYI PALING RIUH KARYA FAJAR SULAIMAN - Selvia; Amirudin Rahim; La Ode Akhiri Zulzaman (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to analyze the characters in Fajar Sulaiman’s novel Sunyi Paling Riuh by applying a structural approach. The research focuses on identifying the types of character traits and their relationships within the story. The method used is qualitative descriptive with library research as the data collection technique, in which textual data such as words, sentences, and narrative descriptions were analyzed to reveal the moral and psychological aspects of the characters. The findings show that the novel presents seven dominant character traits: responsibility, friendliness, compassion, wisdom, helpfulness, perseverance, and uncommunicativeness. These traits are embodied mainly in the protagonist, Dhuha, who undergoes significant personal transformation after the disintegration of his family. The relationships among characters—family, friendship, and educational relations—illustrate moral values of empathy, resilience, and responsibility. Structurally, the novel follows a progression from inner conflict, moral crisis, self-awareness, to emotional recovery. The study concludes that Sunyi Paling Riuh reflects the realities of modern youth struggling with emotional and familial breakdowns while highlighting universal values of love, persistence, and moral strength.